Community Participation in Rural Tourism Decision Making: A Case of Karaikudi, Sivaganga District, Tamil Nadu - Yavana Rani, S.; Jeyakumaran, M.; Geetha, V. (Prabandhan: Indian Journal of Management, 2010)
Tourism is an important mechanism for economic development and the creation of employment opportunities in many countries This has attracted attention from the governments of developing countries looking to maximize economic benefits from tourism development in their own countries. Many developing countries have tried to exploit the tourism industry for economic stimulation by getting foreign investment, capital, and surplus from currency exchange. Local community participation in the decision-making process is always limited or sometimes marginalized, particularly in developing countries (Edelmann 1975; Lea 1988; Timothy 2000). Local communities not only fail to participate in the decision making process, but also fall short in maximising the benefits of tourism development (France 1998; Scheyvens 2003). Researchers (Keogh 1990; Hall 1998; Timothy&Tosun 2003) stress the importance of public participation in the decision-making process during tourism planning and development. Rural Tourism planning involves many stakeholders, such as government agencies, private companies, and non-government organizations (NGOs), which should strengthen the importance of public contribution in the public participation process. In fact, public participation in tourism development does not only relate to the decision-making process and the benefits of rural tourism development, but is also regarded integral to sustainable tourism (D’Amore 1992; Green 1995; Leslie 1993; Murphy 1988).